A Study of Different Similarity Measures on the Performance of Fuzzy Clustering - Mohamed Jafar, OA (International Journal of Computer Sciences and Engineering, 2025)
Data mining is a collection of exploration methods based on advanced analytical tools and techniques for handling huge amount of information. Clustering is a useful technique for discovery of knowledge from a dataset. Distance measure plays an important role in clustering. It is used to measure the similarity or dissimilarity between two data points. Euclidean distance measure is normally used in most clustering methods. Some of the limitations of this measure are inability to handle noise and outlier data points, not suitable for sparse data and clusters with only elliptical shapes. In this paper, fuzzy clustering is proposed using different similarity measures such as non-negative vector similarity coefficient (NVSC), Correlation and Cosine. The performance of the algorithm is compared with various similarity measures using five real life benchmark sets including Wine, Liver Disorders, Pima Indian Diabetes, Haberman’s Survival and Statlog (Heart). Experimental results show that fuzzy clustering based on Cosine similarity measure achieves minimum fitness value, minimum intra-cluster distance and maximum inter-cluster distance on various data sets than other similarity measures.